2019
DOI: 10.1101/623843
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Catalytic Core of DEMETER Guides Active DNA Demethylation in Arabidopsis

Abstract: The Arabidopsis DEMETER (DME) DNA glycosylase demethylates the maternal genome in the central cell prior to fertilization, and is essential for seed viability. DME preferentially targets small transposons that flank coding genes, influencing their expression and initiating plant gene imprinting. DME also targets intergenic and heterochromatic regions, and how it is recruited to these differing chromatin landscapes is unknown. The C--terminal DME catalytic core consists of three conserved regions required for c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Of the remaining five genes, three did not change significantly and two were significantly upregulated in the sporophyte, indicating that the transcriptional regulation of these genes may differ between the central cell and the sporophyte (SI Appendix, Table S2). It is possible that the distinct gene expression patterns in the central cell versus the sporophyte might reflect different cell-specific epigenetic profiles (7,69) or different transcriptional complexes required to express the same DME target genes.…”
Section: Discussionmentioning
confidence: 99%
“…Of the remaining five genes, three did not change significantly and two were significantly upregulated in the sporophyte, indicating that the transcriptional regulation of these genes may differ between the central cell and the sporophyte (SI Appendix, Table S2). It is possible that the distinct gene expression patterns in the central cell versus the sporophyte might reflect different cell-specific epigenetic profiles (7,69) or different transcriptional complexes required to express the same DME target genes.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that Arabidopsis DME can access euchromatin but not heterochromatin without the FACT histone chaperone (Frost et al, 2018). In addition, it was shown that the DME catalytic domain could be recruited to heterochromatins but could not process demethylation effectively (Zhang et al, 2019).…”
Section: Dna Glycosylases Function In Reproductive Cellsmentioning
confidence: 99%
“…The MEDEA promoter-GFP construct contains a 4.238 bp of MEA promoter (upstream of ATG), the HTB2-GFP (nuclear-localized GFP fused with the Arabidopsis histone H2B HTB2 (AT5G22880) protein), and a 2.1 kb MEDEA 3’- end sequence (downstream of the stop codon) concatenated using the Gibson assembly method. The backbone plasmid is a binary plasmid vector, pFGAMh (a hygromycin resistant version of pFGC5941) described before (Zhang et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The backbone plasmid is a binary plasmid vector, pFGAMh (a hygromycin resistant version of pFGC5941) described before (Zhang et al, 2019).…”
Section: Gfp Expressionmentioning
confidence: 99%